একাত্তরের চিঠি - আহমদ, সালাহঊদ্দীন ১৯২৪- (ঢাকা : প্রথমা প্রকাশন, 2009)
Correspondece collection of some martyrs and freedom fighters of the 1971 independence revolution in Bangladesh, written at the time of the revolution.
In Bengali.
Keywords: Revolutionaries -- Bangladesh -- Correspondence; Martyrs -- Bangladesh -- Correspondence; Bangladesh -- History -- Revolution, 1971.